The Impact of the Digitization of Tax Services on the Level of Voluntary Compliance Among Millennial Taxpayers - Pelinta Tarigan; Gatot Nazir Ahmad; Susi Indriyani (Jurnal Indonesia Sosial Sains, 2026)
This research examines the impact of digitization of tax services, digital literacy, and the ease of use of Coretax on the voluntary compliance of millennial taxpayers in Indonesia. The study aims to analyze the direct effects of digitization of tax services, digital literacy, and ease of use of Coretax on voluntary tax compliance, and to identify which factors most significantly influence millennial taxpayers' compliance behavior. This research uses a quantitative approach with a survey of millennials who have used digital tax services. Data were collected using a Likert scale questionnaire and analyzed using Partial Least Squares (SEM-PLS) structural equation modeling analyzed. The results showed that the digitization of tax services had a positive and significant impact on voluntary tax compliance (β = 0.435; p < 0.05). Digital competence (β = 0.357; p > 0.05) and ease of use of coretax (β = -0.245; p > 0.05), on the other hand, showed no significant impact. An R² value of 0.328 means that the model can explain the 32.8% variance in voluntary tax compliance. The results of the study show that the success of digital tax reform depends more on the quality of digital services offered than on the digital literacy component for users and the perceived ease of use of the system. This research provides important insights for the Directorate General of Taxation to optimize the implementation and development of Coretax and digital tax services.